Limited Weight Impact After Switching From Boosted Protease Inhibitors to Dolutegravir in Persons With Human Immunodeficiency Virus With High Cardiovascular Risk: A Post Hoc Analysis of the 96-Week NEAT-022 Randomized Trial. (19th October 2022) - Waters, Laura; Assoumou, Lambert; González-Cordón, Ana; Rusconi, Stefano; Domingo, Pere; Gompels, Mark; de Wit, Stephane; Raffi, François; Stephan, Christoph; Masiá, Mar; Rockstroh, Jürgen; Katlama, Christine; et al.
Abstract: Background: In the NEAT022 trial, virologically suppressed persons with human immunodeficiency virus (HIV) at high cardiovascular risk switching from protease inhibitors to dolutegravir either immediately (DTG-I) or after 48 weeks (DTG-D) showed noninferior virological suppression and significant lipid and cardiovascular disease risk reductions on switching to dolutegravir relative to continuing protease inhibitors. Methods: In post hoc analysis, major endpoints were 48-week and 96-week weight and body mass index (BMI) changes. Factors associated with weight/BMI changes within the first 48 weeks of DTG exposure, proportion of participants by category of percentage weight change, proportions of BMI categories over time, and impact on metabolic outcomes were also assessed. Results: Between May 2014 and November 2015, 204 (DTG-I) and 208 (DTG-D) participants were included. Weight significantly increased (mean, +0.810 kg DTG-I arm, and +0.979 kg DTG-D arm) in the first 48 weeks postswitch, but remained stable from 48 to 96 weeks in DTG-I arm. Switching from darunavir, White race, total to high-density lipoprotein cholesterol ratio <3.7, and normal/underweight BMI were independently associated with higher weight/BMI gains. The proportion of participants with ≥5% weight change increased similarly in both arms over time. The proportions of BMI categories, use of lipid-lowering drugs, diabetes and/or use of antidiabetic agents, and hypertension and/or use of antihypertensive agents did not change within or between arms at 48 and 96 weeks. Conclusions: Switching from protease inhibitors to dolutegravir in persons with HIV with high cardiovascular risk led to modest weight gain limited to the first 48 weeks, which involved preferentially normal-weight or underweight persons and was not associated with negative metabolic outcomes. Clinical Trials Registration: NCT02098837 and EudraCT 2013-003704-39. Abstract : Switching from protease inhibitors to dolutegravir in persons with HIV with high cardiovascular risk led to modest weight gain limited to the first 48 weeks, which involved preferentially normal-weight or underweight persons and was not associated with negative metabolic outcomes. Graphical Abstract: